2003
DOI: 10.1126/science.1090389
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Genes That Enhance the Toxicity of a Mutant Huntingtin Fragment or α-Synuclein

Abstract: Genome-wide screens were performed in yeast to identify genes that enhance the toxicity of a mutant huntingtin fragment or of alpha-synuclein. Of 4850 haploid mutants containing deletions of nonessential genes, 52 were identified that were sensitive to a mutant huntingtin fragment, 86 that were sensitive to alpha-synuclein, and only one mutant that was sensitive to both. Genes that enhanced toxicity of the mutant huntingtin fragment clustered in the functionally related cellular processes of response to stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
320
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(339 citation statements)
references
References 30 publications
16
320
1
2
Order By: Relevance
“…In conclusion, we support a model of yeast toxicity in which overexpressed monomeric synuclein directly coats the plasma and internal membranes via its amphipathic α-helices, disrupting normal membrane processes (including vesicle trafficking [19][20][21], and eventually leading to toxicity. Perhaps the simplest mechanism by which synuclein binding could disrupt membrane processes is a non-specific one.…”
Section: Is Membrane Binding Necessary For Synuclein Induced Yeast Tosupporting
confidence: 73%
See 1 more Smart Citation
“…In conclusion, we support a model of yeast toxicity in which overexpressed monomeric synuclein directly coats the plasma and internal membranes via its amphipathic α-helices, disrupting normal membrane processes (including vesicle trafficking [19][20][21], and eventually leading to toxicity. Perhaps the simplest mechanism by which synuclein binding could disrupt membrane processes is a non-specific one.…”
Section: Is Membrane Binding Necessary For Synuclein Induced Yeast Tosupporting
confidence: 73%
“…We are using the yeast Saccharomyces cerevisiae as an in vivo model system, which exhibits toxicity (defined here as slowed growth) and α-synuclein inclusion formation. 18,19 Wild type and A53T α-synuclein are both toxic and localize to inclusions and the plasma membrane when expressed from multiple GAL promoters, such as those on 2-micron plasmids (high copy number) or from multiple integrated copies. 18,20,21 In contrast, the A30P variant is non-toxic to yeast and is uniformly distributed throughout the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…A screen of the complete set of viable gene deletion strains from yeast that are more sensitive to the heterologous expression of a-synuclein has identified 86 different genes including YGL231c [25]. We found that there was a noticeable decrease in the viability of YGL231cD cells expressing a-synuclein when compared to wild type cells (40.1 ± 2.2% vs. 47.4 ± 1.8%).…”
Section: Yeast Tmem85 Protects Against H 2 O 2 Induced Stressmentioning
confidence: 88%
“…Combinations of these factors must account for their different pathobiologies. Recent studies have started to identify protein-protein and genetic interaction networks for polyQ proteins (6)(7)(8), but the current data do not yet provide a framework for understanding the distinct molecular pathologies caused by different polyQ expansion proteins.…”
mentioning
confidence: 99%